THE ROLE OF AGRICULTURE IN THE ECONOMIC DEVELOPMENT OF THE UZBEK SSR IN THE YEARS AFTER THE SECOND WORLD WAR (Scientific journal of the Fergana State University, 2023)
The article studies the problems of agricultural development of the Uzbek SSR in postwar years. The Soviet leadership entrusted the government of the republic with the task to further develop the cotton production. As a result, agriculture, primarily cotton growing, became a priority in the economy of the republic, which resulted the emergence of a further negative trend in the social and economic development of the Uzbek SSR as a whole.